Incorporating gender, equity, and human rights into the action planning process: moving from rhetoric to action - Sanjeev Sridharan; Joanna Maplazi; Apurva Shirodkar; Emma Richardson; April Nakaima (Taylor & Francis Group, 2016)
Background: Mainstreaming of gender, equity, and human rights (GER) is an important focus of the World Health Organization (WHO) and other UN organizations. This paper explores the role of action plans in mainstreaming GER. This paper is informed by a theory-driven evaluation lens. Design: A theory of change framework explored the following seven dimensions of how action plans can implement mainstreaming of GER: awareness of the foundations of GER; understanding of context; planning to impact GER; implementation for GER; monitoring, evaluation, and learning; planning for sustainability; agenda setting and buy-in. The seven dimensions were used to analyze the action plans. Reviewers also explored innovations within each of the action plans for the seven dimensions. Results: GER mainstreaming is more prominent in the foundation, background, and planning components of the plan but becomes less so along the theory of change including implementation; monitoring and evaluation; sustainability; and agenda setting and buy-in. Conclusions: Our analysis demonstrates that much more can be done to incorporate GER considerations into the action planning process. Nine specific recommendations are identified for WHO and other organizations. A theory-driven approach as described in the paper is potentially helpful for developing clarity by which action plans can help with mainstreaming GER considerations.